2015
DOI: 10.3109/0886022x.2015.1096729
|View full text |Cite
|
Sign up to set email alerts
|

The association of urolithiasis and androgenetic alopecia

Abstract: Objectives: The objective of this study is to investigate whether patients with androgenetic alopecia were at risk in terms of urinary system stone disease. Patients and methods: Patients with no baldness (Hamilton-Norwood Scala [HNS] stage I) were categorized as Group I, those with hair loss in the frontal region (HNS stages II, III, IIIa, and IVa) as Group II, those with hair loss in the vertex region (HNS stage III-vertex, V) as Group III and those with hair loss in both vertex and frontal regions (HNS stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…There were previous studies examining the relationship between AGA and systemic diseases where the Norwood–Hamilton scale, which is the same scale as our study, was used while classifying AGA in these studies 49–51 . Ours was the first to approach this topic in a cohort‐based study design.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There were previous studies examining the relationship between AGA and systemic diseases where the Norwood–Hamilton scale, which is the same scale as our study, was used while classifying AGA in these studies 49–51 . Ours was the first to approach this topic in a cohort‐based study design.…”
Section: Discussionmentioning
confidence: 97%
“…There were previous studies examining the relationship between AGA and systemic diseases where the Norwood-Hamilton scale, which is the same scale as our study, was used while classifying AGA in these studies. [49][50][51] Ours was the first to approach this topic in a cohort-based study design. Similarly, NHANES criteria have been frequently used in epidemiological studies to determine the severity of periodontal disease; we showed successful results in a study examining the relationship between androgenic hormone levels and periodontal disease.…”
Section: Ta B L Ementioning
confidence: 99%